Olympic Art Competition in Hungary - Rixer, Ádám (Advances in Social Sciences Research Journal, 2018)
The present study raises the idea of creating an artistic Olympics to facilitate further scientific, professional and, where approriate, broader social dialogue, taking two dimensions into consideration. On the one hand, it intends to support the realisation of an event of this type in Hungary while articulating valid arguments to emphasise those elements that would make Hungary an ideal organiser. On the other hand, the study offers indicators for further and more thorough scientific examination of the process by outlining the main research directions and methods.